On Contractible J-Saces - Dawood, Narjis A.; Gasim, Suaad G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Jordan curve theorem is one of the classical theorems of mathematics, it states the following : If is a graph of a simple closed curve in the complex plane the complement of is the union of two regions, being the common boundary of the two regions. One of the region is bounded and the other is unbounded. We introduced in this paper one of Jordan’s theorem generalizations. A new type of space is discussed with some properties and new examples. This new space called Contractible -space.